2023
DOI: 10.1002/dmrr.3625
|View full text |Cite
|
Sign up to set email alerts
|

Assisted reproductive technology, risk of gestational diabetes, and perinatal outcomes in singleton pregnancies

Abstract: Aims To evaluate the impact of assisted reproductive technology (ART) on the risk of gestational diabetes mellitus (GDM) in single pregnancies. Materials and Methods We retrospectively collected clinical and anthropometric data of 219ART‐ and 256 age‐ and body mass index (BMI)‐matched women with spontaneous conception screened for GDM. The primary outcome was to evaluate GDM prevalence in ART women. Results There were no differences in age, BMI, and family history of diabetes in the two groups of women. ART‐wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 48 publications
1
0
0
Order By: Relevance
“…The rise in diabetes cases in recent years emphasizes the importance of paying attention to this issue, especially in Asia. Furthermore, Bar-Zeev et al and Bianchi et al found that smoking and assisted reproductive technology were risk factors for gestational diabetes mellitus, which is consistent with the results of our study ( 29 , 30 ).…”
Section: Discussionsupporting
confidence: 93%
“…The rise in diabetes cases in recent years emphasizes the importance of paying attention to this issue, especially in Asia. Furthermore, Bar-Zeev et al and Bianchi et al found that smoking and assisted reproductive technology were risk factors for gestational diabetes mellitus, which is consistent with the results of our study ( 29 , 30 ).…”
Section: Discussionsupporting
confidence: 93%
“…Embryonic factors may stem from the manipulation of embryos during the IVF/ICSI procedure, potentially altering their subsequent development. On the other hand, maternal factors may comprise underlying infertility, advanced age, and the utilization of ovarian stimulation drugs, all of which may contribute to the disparities observed in neonatal outcomes ( 11 , 31 , 32 ). Moreover, it is essential to emphasize an additional pivotal aspect: the augmented significance attributed to embryos acquired through IVF/ICSI by patients.…”
Section: Discussionmentioning
confidence: 99%
“…Lei et al ( 10 ) discovered a significant correlation between ART and an elevated occurrence of gestational diabetes mellitus and intrahepatic cholestasis of pregnancy, in contrast to pregnancies resulting from natural conception. Bianchi et al’s study revealed that gestational diabetes occurs in approximately 50% of women undergoing ART treatment ( 11 ). Conversely, other studies have not identified any noteworthy disparities between IVF/ICSI and NP ( 12 – 14 ).…”
Section: Introductionmentioning
confidence: 99%